Ecosystem Services and Sustainability of Kelulut Stingless Beekeeping - Humaida, Nida; Lawasi, Moh. Andika; Pratiwi, Dian; Bagja Pratama, Boby; Rizkiana Yusnikusumah, Tri (SOCA: Jurnal Sosial Ekonomi Pertanian, 2024)
Kelulut stingless bees play a crucial role as pollinators for numerous crops. Since cultivating honey can contribute to food security and promote sustainable agricultural practices, it is thus essential to identify the ecosystem services provided by kelulut stingless beekeeping for sustainable honey farming. A comprehensive literature review was conducted with the aim of (1) identifying the ecosystem services associated with kelulut stingless beekeeping and (2) determining the factors influencing its sustainability. The literature review used two search databases, Google Scholar and ScienceDirect, with relevant keywords, and the findings were summarized and interpreted by referring to recent studies. Additionally, a SWOT analysis was conducted to assess the factors influencing the sustainability of Kelulut stingless beekeeping. It was revealed that there are three main ecosystem services of stingless bee keeping: provisioning services (honey products), regulating services (pollination, impact on the food chain, and biodiversity), and cultural functions (tourism and education). The sustainability of ecosystem services provided by kelulut stingless beekeeping depends on several factors, such as the strength of the local community, farmers’ skills, and biodiversity, as indicated in the SWOT analysis table. This paper provides valuable insights for future studies, aiding in developing sustainable management strategies for stingless bee colonies and enhancing their productivity based on the characteristics of ecosystem services and their influencing factors